D-DIMER IN HEMODIALYSIS PATIENTS RECEIVING CONTINUOUS AND INTERMITTENT HEPARIN - Derry Heppy Fritiwi; Harun Rasyid Lubis; Adi Koesoema Aman; Herman Hariman (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Haemodialysis is the most widely used kidney replacement therapy in Indonesia and in the world, but the procedure may trigger development on thrombogenesis. Doe to this reason, anticoagulant heparin is given during haemodialysis to prevent the development of thrombus. However, haemostasis monitoring is essential to predict the possibility of heparin induced bleeding. The use of heparin in general needs a machine to regulate continuous heparin administration, nonetheless not all hospitals have that instruments and for this reasons some centre use intermittent heparin injection. The aim of this study is to investigate whether intermittent heparin is as effective as continuous heparin to prevent thrombus formation as well as to prevent bleeding and predict the survival outcome. Patient divided in to two grup from intermittent heparin and continuous heparin in total 50 patient were participated. Platelet count, PT, APTT, TT, fibrinogen, and D-dimer were investigated. The result demonstrates that platelet count, PT, APTT, TT, fibrinogen, and D-dimer were not significantly differed between the groups receiving intermittent and continuous heparin (p >0.05). When the test is compared between intermittent and continuous heparin in pre and post haemodialysis it is clear that there is significant increases in APTT and fibrinogen both in the intermittent and continuous heparin, but D-dimer is increased in continuous heparin only during post haemodialysis. There is no difference in the 1-year survival outcome between intermittent and continuous heparin. In conclusion, intermittent heparin produces less D-dimer increase compared to continuous heparin but it is as effective as continuous heparin. Intermittent heparin may be used as the alternative choice when continuous syringe driver machine is not available.